Perbandingan Desain Pembelajaran ASSURE dan PPSI untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis dan Kemandirian Belajar - Sundayana, Rostina (Institut Pendidikan Indonesia, 2019)
AbstrakPenelitian ini bertujuan untuk mengkaji peningkatan kemampuan pemecahan masalah dan kemandirian belajar matematika siswa kelas VII dengan menggunakan desain pembelajaran ASSURE. Penelitian ini menggunakan metode kuasi eksperimen, dengan desain kelompok kontrol pretes-postes. Pada kelompok kontrol, digunakan desain pembelajaran yang sedang berjalan yaitu desain Prosedur Pengembangan Sistem Instruksional (PPSI).Populasi dalam penelitian ini adalah siswa kelas VII SMP Negeri di Kabupaten Garut yang mencakup sekolah level bawah, tengah, dan atas.Dari masing-masing level tersebut, diambil sampel sebanyak tiga kelompok yaitu kelompok eksperimen 1 (siswa yang mendapat desain pembelajaran ASSURE dengan model Problem Based Learning/A-PBL); kelompok eksperimen 2 (siswa yang mendapat desain pembelajaran ASSURE dengan model Discovery Learning/A-DL) dan kelompok kontrol (siswa yang mendapat desain PPSI dengan model pembelajaran PBL dan DL). Dengan menggunakan teknik analisis data ANOVA, Kruskal-Wallis, Uji Tukey HSD, dan uji Perbandingan Berganda diperoleh kesimpulan dari hasil penelitian ini, secara umum bahwa: peningkatan kemampuan pemecahan masalah dan kemandirian belajar matematika siswa yang mendapat desain pembelajaran ASSURE lebih baik dari siswa yang mendapat PPSI. The Comparison of ASSURE and PPSI Model as Instructional Design to Increase Mathematics Skills in Problem Solving and Self-Directed LearningAbstractThis study is aimed at reviewing the increase of Junior High School Students’ Mathematics skills in problem solving and Self-directed learning by using ASSURE design (Analyze learner characteristics; State standards and objectives; Select methods, media and materials; Utilize media and materials; Require learner participation; and Evaluate and revise). This study used experimental method with pretest-posttest control group design. The population in this study was grade VII students of State Junior High Schools located in Garut Regency consisting of schools with lower level, middle level, and top level. From the schools which had been randomly selected, three classes were also randomly selected to take as sample. The first two classes used ASSURE model as instructional design by applying Problem Based Learning (A-PBL) and Discovery Learning (A-DL) respectively. Meanwhile, the third class used conventional instructional design by applying Problem Based Learning and Discovery Learning (K-PBL/DL). By using ANOVA data analysis techniques, Kruskal-Wallis, Tukey HSD Test, and Multiple Comparison tests are concluded in general, the conclusion drawn based on the results of this study is that the increase of students' Mathematics skills in problem solving and Self-directed learning who were taught by using ASSURE model showed better results than those who were taught by using conventional model.